Diminution Reality Objects –based on Image Depth - Resen, Sallama; Ibrahim, Muthanna (International Journal of Psychosocial Rehabilitation, 2020)
Augmented Reality (AR) applications increasing popularity in a variety of industries, education, and marketing. AR techniques combined with the real world with virtual objects enable augmented reality applications to provide a better understanding and display of information for products. Diminished Reality Objects (DRO) techniques that visually eliminate real objects from AR applications. While an increasing interest in the Diminution Reality technique can be observed, most of the diminished reality research focuses on the consistency of the real–virtual and texture generated on a marker area. This paper handles the preservation depth consistency from edges and planar regions to build a depth map In order to develop DRO methods. the depth mask is built to this method, which has been consisting of two-stage run concurrence and each stage associated with error measuring to corrects stage. Results instantly, which are Planarity and Boundary Depth techniques. The proposed method evaluated on RGB images dataset acquired by the digital camera with high-properties. The authenticity of the proposed method is displayed in experimental results with a variety of criteria measurements.